'Quixote' and phraseology: a proposal for teaching Spanish - González Cobas, Jacinto (Didáctica. Lengua y Literatura, 2019)
In the past years a debate has been opened concerning the use of literary texts in the SFL lessons, mainly forgotten in the first years of the Communicative Approach. This has impeded the didactic exploitation of quite a few literary works, lines of action that the Quixote could not avoid. This article is part of a framework in which it is considered that literature can make interesting contributions in the process of teaching/learning languages. The Quixote generates curiosity among learners, it allows the imbrication of the linguistic and sociocultural competence and constitutes an important sample of phraseological units built with verbs of movement. In this research I make some considerations about the presence of literature in the SFL classroom, about the Quixote and the phraseology contained in it, while I present a didactic proposal (a treasure hunt) to bring the figure of Cervantes, the Quixote and part of the phraseology used in this work to the SFL class.
Keywords: treasure hunting; SFL; phraseology; Quixote; phraseological units